Does Green Banking Disclosure Improve Banking Financial Performance In The Asean Region? - Rochman Arif; Bandi, Bandi; Agung Nur Probohudono; Djuminah, Djuminah (INFOKUM, 2025)
This study aims to find empirical evidence of the influence of green banking disclosure on the financial performance of banks in the ASEAN region. This type of research is quantitative research using a statistical approach. The population in this study were banking companies in the ASEAN region, as many as 168 banks from 2018-2023 as samples in this study and 984 observation data were obtained. The data analysis tool in this study used panel data regression with the help of the STATA version 12 tool. The results of the study showed that green banking disclosure had a positive and significant influence on banking performance as measured using ROA and ROE.